On the application and generation of subsensory electrical nerve stimulation for the improvement of vibration perception in patients with HIV-related sensory neuropathy - Karpul, David (Department of Medicine, 2020)
This work investigates the application of Subsensory Electrical Noise Stimulation (SENS) to improve symptoms of HIV-related peripheral sensory neuropathy (HIVPN). HIV-PN occurs in roughly half of the 5 million people in South Africa with HIV. The disease has been shown to reduce quality of life and increase the risk of secondary ailments. Currently there is no treatment available. Previously, SENS has shown promise to improve tactile sensitivity in healthy populations and elderly individuals with peripheral neuropathic desensitisation. This work first establishes if SENS can improve the peripheral sensitivity of patients with HIV-PN, and secondly addresses practical aspects of using SENS in a therapeutic context. The vibrotactile sensitivity deficits of participants with HIV-PN and a matched control cohort is documented and analysed. It is found that HIV-PN participants have reduced sensitivity at all tested vibration frequencies (25 Hz, 50 Hz and 128 Hz), but especially at low frequencies. The interaction with vibration frequency indicates that HIV-PN may interact differently with different types of peripheral mechanoreceptors. SENS is then applied at four different amplitudes in an attempt to improve perception thresholds of the three vibration frequencies. SENS was shown to generally have a beneficial effect on 50 Hz vibration sensitivity for low SENS amplitudes. It had no effect, or a detrimental effect, at high SENS amplitudes, and also for 25 Hz and 128 Hz vibration frequencies. This work is also the first to document measures of pain with interventions of this type. No clear effects of SENS on sensations of pain were observed, which is a vital outcome if the therapy is to be developed further, since neuropathic pain is a frequent symptom of HIV-PN. The application of SENS as a practical therapy requires the accurate measurement of the participant’s electrical perception threshold, and a wearable device to apply the electrical signal on an ongoing basis. Research into the stability of electrical perception thresholds specifically aimed at subthreshold signals that would improve tactile sensitivity is presented. It was found that these thresholds vary wildly and correlated very little with possible explanatory variables, which introduces a new challenge for the development of SENS in future research. Currently there are no devices available to apply SENS in non-laboratory settings or for continuous use. The electronic design of a stimulator for using SENS as a wearable intervention is presented and characterised. The circuit is an efficient, low-power voltage to current converter that generates high voltages (120 V peak to peak) from a small, low-voltage rechargeable battery. The design and testing of control and instrumentation circuitry, as well as the addition of various safety and interface features is also documented. The battery life of the circuit is tested to operate for up to 33 hours and the circuit is tested to operate as expected in vivo. The results of this work demonstrate the potential viability of SENS as a therapy for HIV-PN, reveals the variability of electrical perception thresholds, explores the measures of pain for SENS interventions, and provides a complete and thoroughly tested design and implementation of an unparalleled electronic stimulator for nonlaboratory environments. The conclusions of this work form both a strong theoretical and practical basis for future SENS intervention research.